Perception of people with visual disability on guidance and counselingservice in self-concept development - Elvina Oktavia; A. Muri Yusuf; Yanuar Kiram (International Conferences on Educational, Social Sciences and Technology)
The various experiences of people with visual disability about guidance and counseling in Bina Netra Social House “Tuah Sakato” Padang caused kinds of perceptions. The research were to describe the perception of low vision and total blindness and also the distinct perception about guidance counseling in self concept development. The type of the research was comparative descriptive. By using purposivesampling method, about 30 of them were chosen to be the sample. The instruments used was Guidance and Counseling Perception Scale (GCPS) which was read by the researcher. Data of the research was analyzed by using Mann-Whitney U Test. The result of the research shows there is no significant differenceperception between people with low vision and total blindness. It means both of them have good perception about guidance and counseling in self concept development.